A low temperature forming method for high rare earth content magnesium alloy

By adding deformable Ti particles to rare earth magnesium alloys and using extrusion and annealing processes, the problem of difficulty in low-temperature forming of rare earth magnesium alloys is solved, and the low-temperature forming and mechanical properties of high rare earth magnesium alloys are improved.

CN116814996BActive Publication Date: 2025-02-14TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310913199.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-02-14
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

Rare earth magnesium alloys are difficult to form when the rare earth content exceeds 10 wt.%, and high-temperature forming has high requirements for equipment and consumes a lot of energy, which affects the development of green and low-carbon.

Method used

Low-temperature forming of rare earth magnesium alloy is achieved by adding deformable Ti particles to the rare earth magnesium alloy and using a process combining extrusion and annealing.

Benefits of technology

It effectively reduces the forming temperature, improves the mechanical properties of rare earth magnesium-based composite materials, and realizes low-temperature forming of high-risk earth magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116814996B_ABST
    Figure CN116814996B_ABST
Patent Text Reader

Abstract

A low-temperature forming method for a magnesium alloy with a high rare earth content belongs to the technical field of magnesium alloy materials, solves the technical problems of high hardness, difficult deformation and high forming temperature required for rare earth magnesium alloys, and the solution is: using Mg-Gd-Y-Zn alloy as a matrix and deformable Ti particles as a reinforcement phase to prepare a Tip / rare earth magnesium-based composite material, by regulating the stirring temperature, stirring speed and stirring time, a rare earth magnesium-based composite material with uniform Ti particle distribution and no obvious agglomeration on the matrix surface is obtained, and on this basis, low-temperature forming of rare earth magnesium alloys is further realized by extrusion deformation and annealing processes. The Tip / rare earth magnesium-based composite material prepared by the present invention has a yield strength of 324.5MPa, a tensile strength of 361.5MPa, and an elongation of 9.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy materials, and particularly relates to a low-temperature forming method for a magnesium alloy with a high rare earth content. Background Art

[0002] Rare earth magnesium alloys have excellent room temperature and high temperature mechanical properties and good creep resistance, and are capable of performing service tasks in high temperature and high stress environments. Therefore, they are widely used in important industries such as aerospace, national defense, military industry, and automobiles. They have become the most promising high-performance magnesium alloys in the new century and are highly valued by scientific researchers. Among them, Mg-Gd-Y-Zn alloys have shown great development potential.

[0003] However, for rare earth magnesium alloys, when the rare earth content exceeds 10wt.%, the profile is difficult to form. In order to achieve its forming, the forming temperature is generally higher than 450℃. On the one hand, the higher the deformation temperature, the larger the grain size, and the lower its mechanical properties; on the other hand, high-temperature forming has high requirements on equipment and causes energy consumption, which is not conducive to promoting green and low-carbon development. Therefore, lowering the forming temperature is an important direction for the future development of high rare earth magnesium alloys. Summary of the invention

[0004] In order to overcome the deficiencies in the prior art and solve the technical problems of high hardness, difficulty in deformation and high forming temperature required for rare earth magnesium alloys, the present invention provides a low-temperature forming method for a magnesium alloy with a high rare earth content, wherein deformable Ti particles are added to the rare earth magnesium alloy as a reinforcing phase, and the low-temperature forming of the rare earth magnesium alloy is achieved through the coordinated deformation of the Ti particles and the rare earth magnesium matrix.

[0005] The design concept of the present invention is:

[0006] On the one hand, the present invention prepares a rare earth magnesium-based composite material in which the Ti particles are evenly dispersed and there is no obvious agglomeration on the surface by adding deformable Ti particles as reinforcement to a high rare earth magnesium alloy;

[0007] On the other hand, the present invention improves the mechanical properties of high rare earth magnesium-based composite materials by combining extrusion and annealing. Extrusion is an effective deformation method to improve the structure and performance of cast magnesium alloys. Because the material is subjected to strong triaxial compressive stress during extrusion deformation, casting defects can be significantly eliminated, the structure is refined, and the plastic deformation of the blank is facilitated. Therefore, the extrusion forming process is very important for controlling the structure and performance of magnesium alloys; annealing treatment can eliminate the residual internal stress in the material after extrusion, which is conducive to the release of dislocations, thereby ensuring the low-temperature forming performance of high rare earth magnesium alloys;

[0008] In summary, the present invention selects Mg-Gd-Y-Zn alloy as the matrix and deformable Ti particles as the reinforcement, the particle size of the Ti particles is 20um~30um, and prepares a high rare earth magnesium-based composite material with uniform Ti particle distribution and no obvious agglomeration on the surface; the mechanical properties of the high rare earth magnesium-based composite material are improved by a process combining extrusion and annealing, and low-temperature forming of the high rare earth magnesium alloy is achieved.

[0009] The present invention is achieved through the following technical solutions:

[0010] A low temperature forming method for a magnesium alloy with a high rare earth content comprises the following steps:

[0011] S1. Pretreatment of Ti powder: First, wrap Ti powder with Zn foil, and record the weight of Ti powder and the weight of Zn foil respectively; then, put Ti powder wrapped with Zn foil into a container wrapped with Al foil, and put it into a drying furnace for preheating at a temperature of 140°C to 180°C, and reserve it for use in the next step;

[0012] S2. Raw material selection: First, cut a magnesium block according to the size of the crucible, grind the magnesium block, magnesium-gadolinium master alloy and magnesium-yttrium master alloy with an angle grinder to remove the oxide scale on the surface; then, weigh the magnesium block, zinc particles, magnesium-gadolinium master alloy and magnesium-yttrium master alloy, so that the composition and mass percentage content of each element in the raw materials are: zinc: 3wt.%, gadolinium: 5wt.%~10wt.%, yttrium: 2wt.%, and the rest is magnesium; finally, wrap the weighed raw materials with plastic wrap respectively and keep them for use in the next step;

[0013] S3, placing a clean crucible into a melting furnace for preheating, taking out the clean crucible after it is preheated to 430°C-550°C, evenly applying a coating agent on the inner wall of the crucible, and then placing it into the melting furnace;

[0014] S4, heating the smelting furnace to 740°C-760°C, and after the surface of the crucible turns yellow, placing the magnesium block weighed in step S2 into the crucible and heating until the magnesium block is completely melted, and continuously introducing protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid;

[0015] S5, the smelting furnace is cooled to 710°C-720°C, the oxide layer on the surface of the magnesium liquid is removed, the zinc particles weighed in step S2 are added to the magnesium liquid and stirred for 0.5min-1.5min, and then kept warm for 10min-20min;

[0016] S6, after the heat preservation of step S5 is completed, the alloy liquid is naturally cooled to 600°C~640°C with the smelting furnace, and the alloy liquid is in a semi-solid state. After the oxide layer on the surface of the semi-solid alloy melt is removed, a stirring paddle is placed, and the stirring device is started for mechanical stirring. After the semi-solid alloy melt forms a stable vortex, the Ti powder pretreated in step S1 is taken out, and the Ti powder is added to the semi-solid alloy melt together with the Zn foil, wherein the added amount of Ti powder accounts for 5%~15% of the volume fraction of the total melt, and the stirring paddle is withdrawn after stirring for 10min~20min; metal Ti has high plasticity and is easy to deform, and its elongation at room temperature is greater than 20%. It is added to the rare earth magnesium alloy as a reinforcing phase, and can be co-deformed with the matrix, which is conducive to realizing the continuous transfer of load and uniform plastic deformation between the rare earth magnesium matrix and the reinforcing phase Ti particles at low temperature, and is conducive to improving the ductility of the rare earth magnesium-based composite material;

[0017] S7, mechanical stirring: the melting furnace is heated to 700°C-740°C again, the oxide layer on the surface of the alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy weighed in step S2 are placed into the alloy melt. After the alloy is melted, a stirring paddle is placed again for mechanical stirring for 5min-20min. After the mechanical stirring is completed, the stirring paddle is removed;

[0018] S8, ultrasonic dispersion treatment: remove the oxide layer on the surface of the alloy liquid obtained in step S7, insert the ultrasonic working rod preheated to 480°C to 500°C into the alloy liquid 20mm below the liquid surface, perform ultrasonic dispersion for 5min to 8min, then take out the ultrasonic working rod, keep it warm and let it stand for 3min to 5min;

[0019] S9, casting: preheat the casting mold to 400°C~500°C, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8, then cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 400KN, the pressure holding time is 180s~300s, after the die casting is completed, take out the ingot and cool it naturally to room temperature to obtain a Tip / rare earth magnesium-based composite material ingot;

[0020] S10, extrusion forming and annealing treatment: First, the Tip / rare earth magnesium-based composite material ingot obtained in step S9 is cut into several extrusion blocks, and the surface of the extrusion blocks is polished clean; then, the extrusion blocks are placed in an extrusion mold and preheated to 360°C, and a press is used to hot extrude the extrusion blocks, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1; finally, the extruded rod cooled to room temperature is placed in a muffle furnace with a heating temperature of 360°C and kept warm for 30 minutes. After the insulation is completed, it is quickly taken out and quenched to obtain the Tip / rare earth magnesium-based composite material.

[0021] Furthermore, in step S2, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%.

[0022] Furthermore, in step S3, the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water.

[0023] Furthermore, in step S4, the shielding gas is a mixed gas consisting of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1.

[0024] Furthermore, the sum of the weight of the Zn foil in step S1 and the weight of the zinc particles in step S2 is the total content of the Zn element in the Tip / rare earth magnesium-based composite material obtained in step S10.

[0025] Furthermore, in the steps S5 to S9, a scraper spoon is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the scraper spoon is coated with a coating agent.

[0026] The beneficial effects of the present invention are:

[0027] The present invention adds deformable Ti particles as reinforcement to the rare earth magnesium alloy to prepare a rare earth magnesium-based composite material with uniform Ti particle distribution and no obvious surface agglomeration; the microstructure and mechanical properties of the rare earth magnesium-based composite material are further improved by a process combining extrusion and annealing, and low-temperature forming of high rare earth magnesium alloy is achieved. After extrusion and annealing, the yield strength of the rare earth magnesium-based composite material is 324.5MPa, the tensile strength is 361.5MPa, and the elongation is 9.1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a heating mechanism curve diagram of the Tip / Mg-10Gd-2Y-3Zn composite material prepared in Example 1;

[0029] Figure 2 The microstructure morphology of the as-cast Tip / Mg-10Gd-2Y-3Zn composite material prepared in Example 1;

[0030] Figure 3 This is a microstructure morphology of the extruded Tip / Mg-10Gd-2Y-3Zn composite material prepared in Example 1;

[0031] Figure 4This is a microstructure morphology of the annealed Tip / Mg-10Gd-2Y-3Zn composite material prepared in Example 1;

[0032] Figure 5 This is a comparison diagram of the stress-strain curves of the cast and annealed Tip / Mg-10Gd-2Y-3Zn composite materials prepared in Example 1. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1

[0034] like Figure 1 A low temperature forming method of a magnesium alloy with a high rare earth content is shown, comprising the following steps:

[0035] S1. Pretreatment of Ti powder: First, wrap Ti powder with Zn foil, and record the weight of Ti powder and the weight of Zn foil respectively; then, put Ti powder wrapped with Zn foil into a container wrapped with Al foil, and put it into a drying furnace for preheating at 140°C for use in the next step;

[0036] S2. Raw material selection: First, cut a magnesium block according to the size of the crucible, grind the magnesium block, magnesium-gadolinium master alloy and magnesium-yttrium master alloy with an angle grinder to remove the oxide scale on the surface, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%, the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%; then, Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloy and magnesium-yttrium master alloy, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 5wt.%, yttrium: 2wt.%, and the rest is magnesium; finally, wrap the weighed raw materials with plastic wrap respectively for use in the next step; the sum of the weight of the Zn foil in step S1 and the weight of the zinc particles in step S2 is the total content of the Zn element in the final Tip / rare earth magnesium-based composite material;

[0037] S3, put the clean crucible into the smelting furnace for preheating, take out the clean crucible after it is preheated to 430°C, evenly apply a coating agent on the inner wall of the crucible, and then put it into the smelting furnace; the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water;

[0038] S4, heating the smelting furnace to 740°C, and after the surface of the crucible turns yellow, placing the magnesium block weighed in step S2 into the crucible and heating until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0039] S5, cooling the smelting furnace to 710°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles weighed in step S2 into the magnesium liquid and stirring for 0.5min, and then keeping the temperature for 10min;

[0040] S6, after the heat preservation of step S5 is completed, the alloy liquid is naturally cooled to 600°C with the smelting furnace. At this time, the alloy liquid is in a semi-solid state. After the oxide layer on the surface of the semi-solid alloy melt is removed, a stirring paddle is placed, and the stirring device is started for mechanical stirring. After the semi-solid alloy melt forms a stable vortex, the Ti powder pretreated in step S1 is taken out, and the Ti powder is added to the semi-solid alloy melt together with the Zn foil, wherein the added amount of Ti powder accounts for 5% of the volume fraction of the total melt. After stirring for 10 minutes, the stirring paddle is withdrawn;

[0041] S7, mechanical stirring: the melting furnace is heated to 700° C. again, the oxide layer on the surface of the alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy weighed in step S2 are placed into the alloy melt. After the alloy is melted, a stirring paddle is placed again for mechanical stirring for 5 minutes. After the mechanical stirring is completed, the stirring paddle is removed;

[0042] S8, ultrasonic dispersion treatment: remove the oxide layer on the surface of the alloy liquid obtained in step S7, insert the ultrasonic working rod preheated to 480°C into the alloy liquid 20mm below the liquid surface, and after ultrasonic dispersion for 5 minutes, take out the ultrasonic working rod and keep it at the temperature for 3 minutes;

[0043] S9, casting: preheat the casting mold to 400°C, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8, then cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 400KN, the pressure holding time is 180s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain the Tip / rare earth magnesium-based composite material ingot, the microstructure morphology of the cast Tip / Mg-7Gd-2Y-3Zn composite material is shown in the figure Figure 2 As shown by Figure 2 It can be seen that the Ti particles in the cast composite material are evenly dispersed, there is no obvious agglomeration and oxidation slag on the surface, and the second phase is distributed along the grain boundary in a discontinuous network; in the steps S5 to S9, a slag scoop is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or alloy liquid, and the surface of the slag scoop is coated with a coating agent;

[0044] S10, extrusion forming and annealing treatment: First, the Tip / rare earth magnesium-based composite material ingot obtained in step S9 is cut into several extrusion blocks, and the surface of the extrusion blocks is polished clean; then, the extrusion blocks are placed in an extrusion mold and preheated to 360°C, and a press is used to hot extrude the extrusion blocks, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1; finally, the extruded rod cooled to room temperature is placed in a muffle furnace with a heating temperature of 360°C and kept warm for 30 minutes. After the insulation is completed, it is quickly taken out and quenched to obtain the Tip / rare earth magnesium-based composite material.

[0045] The microstructure morphology of the extruded Tip / Mg-7Gd-2Y-3Zn composite material is shown in Figure 3 As shown by Figure 3 It can be seen that after extrusion, the Ti particles were obviously elongated, obvious dynamic recrystallization occurred in the matrix, and the grain size was significantly refined compared with the cast composite material.

[0046] The microstructure of the annealed Tip / Mg-7Gd-2Y-3Zn composite material is shown in Figure 4 As shown by Figure 4 It can be seen that the recrystallization rate of the extruded alloy increases and the grain size increases after annealing.

[0047] Depend on Figure 5 It can be seen that the yield strength, tensile strength and elongation of the cast composite material are 99.0MPa, 134.5MPa and 0.93% respectively. After annealing treatment, the yield strength of the composite material is 324.5MPa, the tensile strength is 361.5MPa, and the elongation is 9.1%. Example 2

[0048] A low temperature forming method for a magnesium alloy with a high rare earth content comprises the following steps:

[0049] S1. Pretreatment of Ti powder: First, wrap Ti powder with Zn foil, and record the weight of Ti powder and the weight of Zn foil respectively; then, put Ti powder wrapped with Zn foil into a container wrapped with Al foil, and put it into a drying furnace for preheating at 160°C for use in the next step;

[0050] S2. Raw material selection: First, cut a magnesium block according to the size of the crucible, grind the magnesium block, magnesium-gadolinium master alloy and magnesium-yttrium master alloy with an angle grinder to remove the oxide scale on the surface, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%, the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%; then, Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloy and magnesium-yttrium master alloy, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; finally, wrap the weighed raw materials with plastic wrap respectively for use in the next step; the sum of the weight of the Zn foil in step S1 and the weight of the zinc particles in step S2 is the total content of the Zn element in the final Tip / rare earth magnesium-based composite material;

[0051] S3, put the clean crucible into the smelting furnace for preheating, take out the clean crucible after it is preheated to 500°C, evenly apply a coating agent on the inner wall of the crucible, and then put it into the smelting furnace; the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water;

[0052] S4, heating the smelting furnace to 750°C, and after the surface of the crucible turns yellow, placing the magnesium block weighed in step S2 into the crucible and heating until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0053] S5, cooling the smelting furnace to 715°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles weighed in step S2 into the magnesium liquid and stirring for 1 minute, and then keeping the temperature for 15 minutes;

[0054] S6, after the heat preservation of step S5 is completed, the alloy liquid is naturally cooled to 620°C with the smelting furnace. At this time, the alloy liquid is in a semi-solid state. After the oxide layer on the surface of the semi-solid alloy melt is removed, a stirring paddle is placed, and the stirring device is started for mechanical stirring. After the semi-solid alloy melt forms a stable vortex, the Ti powder pretreated in step S1 is taken out, and the Ti powder is added to the semi-solid alloy melt together with the Zn foil, wherein the added amount of Ti powder accounts for 10% of the volume fraction of the total melt. After stirring for 15 minutes, the stirring paddle is withdrawn;

[0055] S7, mechanical stirring: the melting furnace is heated to 720° C. again, the oxide layer on the surface of the alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy weighed in step S2 are placed into the alloy melt. After the alloy is melted, a stirring paddle is placed again for mechanical stirring for 10 minutes. After the mechanical stirring is completed, the stirring paddle is removed;

[0056] S8, ultrasonic dispersion treatment: remove the oxide layer on the surface of the alloy liquid obtained in step S7, insert the ultrasonic working rod preheated to 490°C into the alloy liquid 20mm below the liquid surface, and after ultrasonic dispersion for 7min, take out the ultrasonic working rod and keep it at the temperature for 4min;

[0057] S9, casting: preheat the casting mold to 450°C, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8, then cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 400KN, the pressure holding time is 240s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a Tip / rare earth magnesium-based composite material ingot; in the steps S5 to S9, a slag scoop is used to remove the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scoop is coated with a coating agent;

[0058] S10, extrusion forming and annealing treatment: First, the Tip / rare earth magnesium-based composite material ingot obtained in step S9 is cut into several extrusion blocks, and the surface of the extrusion blocks is polished clean; then, the extrusion blocks are placed in an extrusion mold and preheated to 360°C, and a press is used to perform hot extrusion forming on the extrusion blocks, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1; finally, the extruded plate obtained by extrusion forming is taken out and placed in a muffle furnace with a heating temperature of 360°C for insulation for 30 minutes. After the insulation is completed, it is quickly taken out and quenched to obtain the Tip / rare earth magnesium-based composite material. Example 3

[0059] A low temperature forming method for a magnesium alloy with a high rare earth content comprises the following steps:

[0060] S1. Pretreatment of Ti powder: First, wrap Ti powder with Zn foil, and record the weight of Ti powder and the weight of Zn foil respectively; then, put Ti powder wrapped with Zn foil into a container wrapped with Al foil, and put it into a drying furnace for preheating at 180°C for use in the next step;

[0061] S2. Raw material selection: First, cut a magnesium block according to the size of the crucible, grind the magnesium block, magnesium-gadolinium master alloy and magnesium-yttrium master alloy with an angle grinder to remove the oxide scale on the surface, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%, the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%; then, Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloy and magnesium-yttrium master alloy, so that the composition and mass percentage content of each element in the raw materials are: zinc: 3wt.%, gadolinium: 10wt.%, yttrium: 2wt.%, and the rest is magnesium; finally, wrap the weighed raw materials with plastic wrap respectively for use in the next step; the sum of the weight of the Zn foil in step S1 and the weight of the zinc particles in step S2 is the total content of the Zn element in the final Tip / rare earth magnesium-based composite material;

[0062] S3, put the clean crucible into the smelting furnace for preheating, take out the clean crucible after it is preheated to 550°C, evenly apply a coating agent on the inner wall of the crucible, and then put it into the smelting furnace; the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water;

[0063] S4, heating the smelting furnace to 760°C, and after the surface of the crucible turns yellow, placing the magnesium block weighed in step S2 into the crucible and heating until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0064] S5, cooling the smelting furnace to 720°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles weighed in step S2 into the magnesium liquid and stirring for 1.5 minutes, and then keeping the temperature for 20 minutes;

[0065] S6, after the heat preservation of step S5 is completed, the alloy liquid is naturally cooled to 640°C with the smelting furnace. At this time, the alloy liquid is in a semi-solid state. After the oxide layer on the surface of the semi-solid alloy melt is removed, a stirring paddle is placed, and the stirring device is started for mechanical stirring. After the semi-solid alloy melt forms a stable vortex, the Ti powder pretreated in step S1 is taken out, and the Ti powder is added to the semi-solid alloy melt together with the Zn foil, wherein the added amount of Ti powder accounts for 15% of the volume fraction of the total melt. After stirring for 20 minutes, the stirring paddle is withdrawn;

[0066] S7, mechanical stirring: the melting furnace is heated to 740° C. again, the oxide layer on the surface of the alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy weighed in step S2 are placed into the alloy melt. After the alloy is melted, a stirring paddle is placed again for mechanical stirring for 20 minutes. After the mechanical stirring is completed, the stirring paddle is removed;

[0067] S8, ultrasonic dispersion treatment: remove the oxide layer on the surface of the alloy liquid obtained in step S7, insert the ultrasonic working rod preheated to 500°C into the alloy liquid 20mm below the liquid surface, and after ultrasonic dispersion for 8min, take out the ultrasonic working rod and keep it at the temperature for 5min;

[0068] S9, casting: preheat the casting mold to 500°C, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8, then cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 400KN, the pressure holding time is 300s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a Tip / rare earth magnesium-based composite material ingot; in the steps S5 to S9, use a slag scoop to remove the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scoop is coated with a coating agent;

[0069] S10, extrusion forming and annealing treatment: First, the Tip / rare earth magnesium-based composite material ingot obtained in step S9 is cut into several extrusion blocks, and the surface of the extrusion blocks is polished clean; then, the extrusion blocks are placed in an extrusion mold and preheated to 360°C, and a press is used to hot extrude the extrusion blocks, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1; finally, the extruded rod cooled to room temperature is placed in a muffle furnace with a heating temperature of 360°C and kept warm for 30 minutes. After the insulation is completed, it is quickly taken out and quenched to obtain the Tip / rare earth magnesium-based composite material.

[0070] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A low temperature forming method for a magnesium alloy with a high rare earth content, characterized in that: The following steps are involved: S1. Pretreatment of Ti powder: First, wrap Ti powder with Zn foil, and record the weight of Ti powder and the weight of Zn foil respectively; then, put Ti powder wrapped with Zn foil into a container wrapped with Al foil, and put it into a drying furnace for preheating at a temperature of 140°C to 180°C, and reserve it for use in the next step; S2. Raw material selection: First, cut a magnesium block according to the size of the crucible, grind the magnesium block, magnesium-gadolinium master alloy and magnesium-yttrium master alloy with an angle grinder to remove the oxide scale on the surface; then, weigh the magnesium block, zinc particles, magnesium-gadolinium master alloy and magnesium-yttrium master alloy, so that the composition and mass percentage content of each element in the raw materials are: zinc: 3wt.%, gadolinium: 5wt.%~10wt.%, yttrium: 2wt.%, and the rest is magnesium; finally, wrap the weighed raw materials with plastic wrap respectively and keep them for use in the next step; S3, placing the clean crucible into a melting furnace for preheating, taking out the clean crucible after it is preheated to 430°C-550°C, evenly applying a coating agent on the inner wall of the crucible, and then placing it into the melting furnace; S4, heating the smelting furnace to 740°C-760°C, and after the surface of the crucible turns yellow, placing the magnesium block weighed in step S2 into the crucible and heating until the magnesium block is completely melted, and continuously introducing protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid; S5, the smelting furnace is cooled to 710°C-720°C, the oxide layer on the surface of the magnesium liquid is removed, the zinc particles weighed in step S2 are added to the magnesium liquid and stirred for 0.5min-1.5min, and then kept warm for 10min-20min; S6, after the heat preservation of step S5 is completed, the alloy liquid is naturally cooled to 600°C~640°C with the smelting furnace, and the alloy liquid is in a semi-solid state. After the oxide layer on the surface of the semi-solid alloy melt is removed, a stirring paddle is placed, and the stirring device is started for mechanical stirring. After the semi-solid alloy melt forms a stable vortex, the Ti powder pretreated in step S1 is taken out, and the Ti powder is added to the semi-solid alloy melt together with the Zn foil, wherein the added amount of Ti powder accounts for 5%~15% of the volume fraction of the total melt, and the stirring paddle is removed after stirring for 10min~20min; S7, mechanical stirring: the melting furnace is heated to 700°C-740°C again, the oxide layer on the surface of the alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy weighed in step S2 are placed into the alloy melt. After the alloy is melted, a stirring paddle is placed again for mechanical stirring for 5min-20min. After the mechanical stirring is completed, the stirring paddle is removed; S8, ultrasonic dispersion treatment: remove the oxide layer on the surface of the alloy liquid obtained in step S7, insert the ultrasonic working rod preheated to 480°C to 500°C into the alloy liquid 20mm below the liquid surface, perform ultrasonic dispersion for 5min to 8min, then take out the ultrasonic working rod, keep it warm and let it stand for 3min to 5min; S9, casting: preheat the casting mold to 400°C~500°C, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8, then cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 400kN, the holding time is 180s~300s, after the die casting is completed, take out the ingot and cool it naturally to room temperature to obtain a Tip / rare earth magnesium-based composite material ingot; S10, extrusion forming and annealing treatment: First, the Tip / rare earth magnesium-based composite material ingot obtained in step S9 is cut into several extrusion blocks, and the surface of the extrusion blocks is polished clean; then, the extrusion blocks are placed in an extrusion mold and preheated to 360°C, and a press is used to hot extrude the extrusion blocks, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1; finally, the extruded rod cooled to room temperature is placed in a muffle furnace with a heating temperature of 360°C and kept warm for 30 minutes. After the insulation is completed, it is quickly taken out and quenched to obtain the Tip / rare earth magnesium-based composite material.

2. The low temperature forming method of a magnesium alloy with a high rare earth content according to claim 1, characterized in that: In the step S2, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%.

3. The low temperature forming method of a magnesium alloy with a high rare earth content according to claim 1, characterized in that: In step S3, the coating agent is composed of talcum powder coating and zinc oxide coating, the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water.

4. The low temperature forming method of a magnesium alloy with a high rare earth content according to claim 1, characterized in that: In step S4, the protective gas is a mixed gas consisting of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:

1.

5. The low temperature forming method of a magnesium alloy with a high rare earth content according to claim 1, characterized in that: The sum of the weight of the Zn foil in step S1 and the weight of the zinc particles in step S2 is the total content of the Zn element in the Tip / rare earth magnesium-based composite material obtained in step S10.

6. The low temperature forming method of a magnesium alloy with a high rare earth content according to claim 1, characterized in that: In the steps S5 to S9, a scraper spoon is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the scraper spoon is coated with a coating agent.

Citation Information

Patent Citations

  • Preparation method of high-strength titaniferous cast magnesium alloy

    CN109252078A

  • Magnesium-based composite material with special three-phase coexistence structure and preparation method thereof

    CN109439985A